2021
DOI: 10.3390/jpm11121267
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Dexamethasone and Dexmedetomidine on Analgesia Duration of Supraclavicular Brachial Plexus Block: A Randomized, Four-Arm, Triple-Blinded, Placebo-Controlled Trial

Abstract: Intravenous dexamethasone and dexmedetomidine, in conjunction with peripheral nerve blockade, have each been reported to prolong the duration of analgesia. This study tested whether combined use further prolongs analgesia duration after supraclavicular brachial plexus block (BPB) in patients undergoing orthopedic upper extremity surgery. One hundred twenty patients were randomized 1:1:1:1 to Control (saline bolus and midazolam infusion [0.05 mg/kg loading, 20 µg/kg/h thereafter]); DMED (saline bolus and dexmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…24 Block failure: presence of pinprick sensation in at least one neural distribution and/or need of another anesthetic technique to proceed surgery. 7,10,22 Duration of surgery: the time from incision to closure of skin.…”
Section: Operational Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Block failure: presence of pinprick sensation in at least one neural distribution and/or need of another anesthetic technique to proceed surgery. 7,10,22 Duration of surgery: the time from incision to closure of skin.…”
Section: Operational Definitionmentioning
confidence: 99%
“… 5 Nowadays ultrasound-guided brachial plexus block is a popular approach for upper limb surgeries as an alternative to general anesthesia. 6 – 8 From the different approaches to brachial plexus block, the supraclavicular approach is an easy and appropriate technique for anesthesia and analgesia in surgeries below the shoulder joint and this study evaluated it. 9 – 11 It provides greater analgesia, maintains stable intraoperative hemodynamics, reduces the stress response, and decreases anesthetic requirement and beneficial for the patients with various cardiorespiratory comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we observed that dexmedetomidine sedation (at a mean dose of 1.6 µg/kg) significantly extended the duration of the blockade's analgesic effects by approximately 3 h [8]. However, we could not replicate this result in our subsequent study, where we used slightly reduced doses (mean of 1.1-1.2 µg/kg) [24]. In the meantime, in a recent cohort study, it was found that the risk of postoperative hypotension increased to about twice the baseline when the total intraoperative dexmedetomidine dose exceeded 50 µg [20].…”
Section: Discussionmentioning
confidence: 64%
“…Four trials assessed the combination versus dexmedetomidine alone, and all showed a greater duration of analgesia with the combination. [14][15][16][17] In two trials, the combination was shown to provide a greater duration of analgesia than placebo. 7,17 In line with the current trial, dexamethasone with dexmedetomidine provided a similar duration of analgesia as dexamethasone alone in two trials, 18,19 while one trial showed evidence of a greater duration with the combination.…”
Section: Discussionmentioning
confidence: 99%